2020
DOI: 10.1111/dth.13653
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of extracorporeal shock waves for keloid treatment: A pilot study

Abstract: Keloids are fibroproliferative skin disorders characterized by the progressive deposition of collagen. Recently, extracorporeal shock wave therapy (ESWT) has been used to treat pathologic scars. Herein, we conducted a study to compare the efficacy of intralesional injections (ILIs) of triamcinolone acetonide (TA) used alone, or in combination with ESWT for keloids. Forty patients were randomized equally into two groups in this 12‐week comparative clinical trial. Group A was treated with TA ILIs and ESWT, and g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…It is also a safe and effective non-invasive treatment for many fibrotic diseases such as myogenic contracture, pathological scars, epidural fibrosis, etc. [13][14][15][16][17][18][19][20]. In this study, extension knee joint contracture in rats was treated in different ways, to explore whether the treatment effect of SPS combined with ESWT is better than single treatment, and to guide clinical practice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also a safe and effective non-invasive treatment for many fibrotic diseases such as myogenic contracture, pathological scars, epidural fibrosis, etc. [13][14][15][16][17][18][19][20]. In this study, extension knee joint contracture in rats was treated in different ways, to explore whether the treatment effect of SPS combined with ESWT is better than single treatment, and to guide clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Extracorporeal shock wave therapy (ESWT) is widely used in musculoskeletal system diseases [ 13 , 14 ]. The mechanical stimulation produced by ESWT has biochemical effects on some cells and affects the cell cycle and metabolic pathways, which can regulate the migration, proliferation, differentiation and apoptosis of fibroblasts, endothelial cells, osteoblasts, and tenocytes [ 15 ]. Relevant studies have shown that ESWT can reduce cell migration and effectively inhibit the expression of TGF-β1, alpha smooth muscle actin (α-SMA), type I collagen, and fibronectin [ 16 ], making it a feasible and cost-effective method for the treatment of pathological scars after burns [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Another study compared the efficacy of Triamcinolon Acetonide injections (TAI) alone, or in combination with SWT, to treat keloids. The SWT group showed significantly greater good to excellent improvements in the patient and observer global assessment [86]. Aguilera-Saëz et al [87] found no significant differences in any of the Vancouver Scar Scale variables, comparing a group of burn patients treated with standard of care with a group additionally treated with SWT.…”
Section: Shockwave Therapymentioning
confidence: 97%
“…23 More recently, a series of clinical studies of ESWT on pathological scars concluded the positive effects of ESWT on scars with different etiologies. 20,[24][25][26][27][28][29][30][31][32][33][34][35][36] A synthesis of existing evidence of human clinical trials may provide more insight into ESWT application. However, no systematic review and meta-analysis of the effects of ESWT on PBPS has been published yet.…”
Section: Introductionmentioning
confidence: 99%
“…Taheri et al found effects of ESWT on improving PBPS in extremities with a prospective quasi‐experimental study and reported that ESWT could improve pain, itching and appearance of the PBPS 23 . More recently, a series of clinical studies of ESWT on pathological scars concluded the positive effects of ESWT on scars with different etiologies 20,24–36 …”
Section: Introductionmentioning
confidence: 99%